An analysis of eco-efficiency in energy use and CO2 emissions in the Swedish service industries (2013)
This study determines the trends in energy efficiency and CO2 emissions of the Swedish service sector using data at the 2-digit level of aggregation for the Swedish service industry over the period 1993-2008, this empirical study examines eco-efficiency in terms of energy efficiency and CO2 emissions based on a number of models. The results show that Swedish service industries increased energy consumption and CO2 emissions during the sample period, whereas energy and CO2 emission intensities have shown a decrease in recent years. Eco-efficiency models based on the Malmquist data envelopment analysis model suggest that Swedish service industries have an excellent potential to increase energy efficiency and reduce CO2 emissions. Second-stage panel data techniques show that energy taxes, investments and labour productive have a significant and positive influence on energy and CO2 emission intensities implying that increasing these variables lead to higher energy efficiency and lower CO2 emission intensity. This analysis demonstrates the importance of designing and applying adequate energy policies that encourage better energy use and management in this industrial sector for the goal of achieving a low carbon economy. © 2012 Elsevier Ltd.